RACHUNKI I LICZBY STAROŻYTNYCH GREKÓW I RZYMIAN - Gawrysiak, Piotr (Zeszyty Prawnicze, 2017)
Ancient Greek and Roman Numerical Notation and Counting Aids Summary The abilities to count and write down numbers are usually regarded as trivial, while in fact these skills are early technologies that significantly influenced the development of science, trade, culture and law. The lack of understanding of the way in which numerical information was conveyed among people and the ways in which daily computations - such as taxes, livestock accounts, prices etc. - were carried out, might lead to improper reasoning about the culture itself. It is, therefore, useful to know the basics of „daily” mathematics used by Greeks and Romans while studying – for example - Roman law. In this paper some basic information regarding the numerical notation used in ancient Greece and Rome is presented. This includes Roman numerals with examples of mathematical operations performed with their aid and two Greek numerical systems, namely herodianic and attic. Early aids to computation are also discussed, including finger reckoning and the abacus.